Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1128/jvi.01350-19
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Capsid Protein VP1 Interacts with Host Ribosomal Protein SA To Maintain Activation of the MAPK Signal Pathway and Promote Virus Replication

Abstract: Foot-and-mouth disease virus (FMDV) is the causative agent of foot-and-mouth disease, a highly contagious, economically important viral disease. The structural protein VP1 plays significant roles during FMDV infection. Here, we identified that VP1 interacted with host ribosomal protein SA (RPSA). RPSA is a viral receptor for dengue virus and classical swine fever virus infections. However, the incubation of susceptible cells using the anti-RPSA antibodies did not block the infection of FMDV. Overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…HIV-1 Tat inhibits cell proliferation via an interaction with RPS3 and increases the level of RPS3 in the nucleus, thereby disrupting mitotic spindle formation during HIV-1 infection (Kim and Kim 2018 ). FMDV VP1 inhibits the antiviral response of RPSA by interacting with RPSA to promote FMDV replication (Zhu et al 2019 ). Binding of viral proteins to specific RPs plays a crucial role in viral infection.…”
Section: Alterations In Functional Characteristics Of Rps For Viral Tmentioning
confidence: 99%
“…HIV-1 Tat inhibits cell proliferation via an interaction with RPS3 and increases the level of RPS3 in the nucleus, thereby disrupting mitotic spindle formation during HIV-1 infection (Kim and Kim 2018 ). FMDV VP1 inhibits the antiviral response of RPSA by interacting with RPSA to promote FMDV replication (Zhu et al 2019 ). Binding of viral proteins to specific RPs plays a crucial role in viral infection.…”
Section: Alterations In Functional Characteristics Of Rps For Viral Tmentioning
confidence: 99%
“…Studies has shown that DNAJA3 can significantly reduce the inhibitory effect of VP1 on SeV-induced IRF3 phosphorylation, dimerization, and nuclear localization through the lysosomal pathway, thus reducing the antagonism on the IFN-β signal pathway and inhibiting FMDV replication ( Zhang et al, 2019 ). In addition, VP1 can also act on ribosomal protein SA (RPSA) to weaken its inhibitory effect on the mitogen-activated protein kinase (MAPK) pathway, which is conducive to the FMDV replication ( Zhu et al, 2020 ). VP2 may indirectly inhibit the host’s type I IFN response pathway by interacting with the host protein heat shock protein family B [small] member 1 (HSPB1) to enhance viral replication, but the mechanism needs to be further elucidated ( Sun et al, 2018 ).…”
Section: Fmdv Proteins Regulate Host Innate Immunitymentioning
confidence: 99%
“…Another study suggested that the activation of the mitogen-activated protein kinase (MAPK) pathway is essential for FMDV replication. FMDV VP1 interacts with host ribosomal protein SA (RPSA) to continually activate the MAPK signal pathway and promote virus replication by inhibiting the RPSA-mediated function [59] (Figure 2, Table 1).…”
Section: Vp1mentioning
confidence: 99%
“…Ribosomal protein SA VP1 interacts with RPSA to maintain the activation of MAPK signal pathway and promote virus replication [59].…”
Section: Rpsamentioning
confidence: 99%